A Framework for the Analysis of Financial Reforms and the Cost of official Safety Nets - Isard, Peter (IMF Working Papers; Working Paper ;, 1992)
This paper builds a multiperiod, general equilibrium framework for analyzing the macroeconomic effects of financial reforms in developing countries and the costs of maintaining official safety nets under the financial system during such reforms. While a financial liberalization yields efficiency gains, adverse macroeconomic effects can arise if the creditworthiness of the nonfinancial sector is weak. In this situation, financial liberalization may also increase the authorities' expected deposit insurance funding obligations even with strong prudential supervision. Moreover, given the distortions in a repressed financial system, an increase in the required bank capital-asset ratio may increase the funding obligations associated with deposit insurance, particularly when the debt-servicing capacity of nonfinancial firms is low.